The use of litho-geochemistry in the determination of rock alteration of Onto deposit drill core - Perdana, Galih Lutfihadi; Wibowo, Nurhadi; Pratiwinda, Rachmat (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2024)
The alteration description method from drilling core samples in the Onto Cu-Au deposit uses SWIR spectroscopy with certain core sample interval (0.5-1m) using an ASD (Analytical Spectral Device) tool at work site, however when SWIR spectroscopy data is sometimes not available or cannot be used due to the difficulty in determining the boundaries of its alteration zones. Thus, in those case, the rock chemical analysis can be used as complement and reinforcement data in consideration of determining the boundaries of alteration zones. The research was specifically undertaken involving 5 drilling holes which are considered to represent the entire Onto Cu-Au deposit located on Sumbawa Island, West Nusa Tenggara Province, Dompu and Bima Regencies. Litho-geochemistry for drill core is a crucial activity in completing drill core logging and defining final intervals for rock alteration before moving on to the geological modeling phase. The current research method is utilizing the various elements are assessed in terms of their effectiveness for determining or clarifying rock and alteration types, beginning with the most utilized elements, and concluding with ones that are of little use or should be mostly ignored.The alteration of drill hole samples was assessed by combining various geochemical element signatures, including TiO2, Al2O3, FeO, NaO2, CaO, K2O, Pb, Zr, Sr, S, Cu, and Au. Al2O3 values can be used to assess intensity in advanced argillic alteration, on scale of 0 to 17 %, values >10 % indicate mild leaching, 5-10 % moderate and <5 % intense leaching with associated development of vuggy residual quartz. Element CaO, MgO and Na2O value increase drastically from <0.05% to > 5% indicates at the edge of advance argillic alteration (7b) to Potassic or chloritic-phyllic alteration (12 & 8a).At Onto drill core the litho-geochemistry has limitation to distinguish the vuggy residual quartz porous and silicified alteration (4 & 5), it will rely on the visual logging conducted and assessed by field geologist on site. In other case to distinguish between K-Alunite and Na-alunite alteration (6a & 6b) requires a spectral reflection SWIR spectroscopy of its core sample, with this limitation is also applied for Quartz pyrophyllite and Quartz-diaspore alteration (7a & 7b). The determination of rock alteration is playing a significant part in the construction of the Onto geology model for further use in mineral resource classification and estimate; in some extent, the alteration is being used for metallurgy domaining and geotechnical rock characteristic investigation for future underground mining design. Key words: Litho-geochemistry, Onto deposit, Rock alteration core logging